Proses dan Pelaksanaan Rasulullah Shallallahu `alaihi Wa Sallam dalam Melakukan Kepemimpinan - Siti Hadiyanti Dini Islamiati; Masyitoh (Jurnal Dirosah Islamiyah, 2024)
Rasulullah SAW was sent at a time when pre-Islamic Arab society (jahiliyah) was in a very worrying condition, with various forms of moral, social and political damage. Rasulullah SAW came to bring Islamic teachings which changed the entire structure of social life, eliminated injustice, and upheld justice and equality in society. This article will comprehensively review the concept of leadership in Islam, as well as provide information on the leadership role of the Prophet Muhammad. The research conducted was qualitative research. The data collection technique uses the library research method, namely by observing various literature related to the problems in the research, in the form of papers, books, notes and reports of previous research results. The results of this research are that in his leadership, the Prophet Muhammad demonstrated various principles and methods that are very relevant and applicable today. He practices an inclusive leadership style, filled with wisdom, justice and compassion. As a leader, he not only managed worldly affairs but also instilled deep spiritual values ​​in his followers. This makes his leadership a model that is worth studying and implementing in various modern leadership contexts